Voluntary disclosure of intellectual assets and intellectual liabilities - Manassian, Armond (2012)
The economical shift into knowledge and information management can explain the increased importance of intellectual capital as a research and business topic. Research on intellectual capital has been mainly centred on intellectual assets. Our research is centred on the determinants of the disclosure of Intellectual Assets and Intellectual Liabilities in the United Arab Emirates. Therefore, the objective of this specific paper is to conduct a comprehensive review of the literature of intellectual assets and intellectual liabilities, in order to highlight the gaps in literature which we will deal with in our future research. We seek to review some of the most significant extant literature on intellectual capital disclosure and its development path. The first part of this paper emphasizes important theoretical and empirical contributions relating to the definitions and categorizations of intellectual assets and intellectual liabilities, intellectual capital reporting models, determinants of voluntary intellectual capital disclosure, and legal framework perspective of intellectual capital disclosure vis-à-vis IFRS and US GAAP. It aims to prove that no legal or regulatory framework exists for Intellectual Capital disclosure. The second part of this paper provides an executive summary of the main findings of the reviewed studies on voluntary Intellectual Capital Disclosure, including methodologies and proxies used, variables studies, and main findings. The final part identifies possible future research issues into the nature, impact, and value of intellectual capital reporting. The results and findings of our study indicate that there is a wealth of literature on intellectual capital disclosure, with a focus on intellectual assets. Very few researchers have considered the impact of intellectual liabilities. There are several determinants of intellectual capital disclosure, including: industry, size, age, performance, ownership structure, auditors, culture/nationality, economic conditions, and time. In addition, there is a lack of a regulatory framework for intellectual capital reporting. Regarding the methodology employed, we conduct a comprehensive literature review by investigating leading peer-reviewed, refereed journals in the area of intellectual capital, including, but not limited to: Journal of Intellectual Capital, Journal of Knowledge Management, Journal of Accounting Research, European Accounting Review, and others. We study around 400 journal articles covering the period from 1945 until 2011. However, this study has some limitations, which include the restrictions that some valid studies on intellectual capital disclosure have been conducted, but cannot be accessed due to not being published in peer-reviewed journals. In terms of practical implications, the findings of this study serve as a guide and reference for researchers on intellectual capital disclosure, as it summarizes the findings of the main studies over a period 15 years. This is one of the few studies that provide a recent, comprehensive examination of the intellectual capital disclosure literature, while incorporating both: intellectual assets and intellectual liabilities. Existing literature has overlooked a very major component of intellectual capital disclosure, which is intellectual liability. This calls for an original research that can fill these gaps and extend the existing literature.